Prognostic risk of immune-associated signature in the microenvironment of brain gliomas - Tao, Yaling; Zhu, Junqi; Yu, Xiaoling; Cong, Huaiwei; Li, Jinpeng; Cai, Ting; Chen, Qian (Frontiers in Genetics, 2023)
Understanding the key factors in the tumor microenvironment (TME) that affect the prognosis of gliomas is crucial. In this study, we sought to uncover the prognostic significance of immune cells and immune-related genes in the TME of gliomas. We incorporated 970 gliomas patient data from the CGGA database as the training set, and an additional 666 samples from the TCGA database served as the validation set. From our analysis, we identified 21 immune-related differentially expressed genes (DEGs) in the TME, which holds implications for glioma prognosis. Based on these genes, we constructed a prognostic risk model on the 21 genes. The prognostic risk model demonstrated robust performance with an AUC of 0.848. Notably, the risk score derived from the model emerged as an independent prognostic factor of gliomas, with high-risk scores indicative of an unfavorable prognosis. Furthermore, we observed that high infiltration levels of certain immune cells -namely activated dendritic cells, M0 macrophages, M2 macrophages and regulatory T cells (Tregs) -correlated with an unfavorable glioma prognosis. In conclusion, our findings suggested that the TME of gliomas harbored a distinct immune-associated signature, comprised of 21 immune-related genes and specific immune cells. These elements significantly influence prognosis and present potential as novel indicators in the clinical assessment of glioma patient outcomes.